Metal-organic frameworks for advanced transducer based gas sensors: review and perspectives - Majhi, Sanjit Manohar; Ali, Ashraf; Rai, Prabhakar; Greish, Yaser E; Alzamly, Ahmed; Surya, Sandeep G; Qamhieh, Naser; Mahmoud, Saleh T (Nanoscale advances, 2022)
The development of gas sensing devices to detect environmentally toxic, hazardous, and volatile organic compounds (VOCs) has witnessed a surge of immense interest over the past few decades, motivated mainly by the significant progress in technological advancements in the gas sensing field. A great deal of research has been dedicated to developing robust, cost-effective, and miniaturized gas sensing platforms with high efficiency. Compared to conventional metal-oxide based gas sensing materials, metal-organic frameworks (MOFs) have garnered tremendous attention in a variety of fields, including the gas sensing field, due to their fascinating features such as high adsorption sites for gas molecules, high porosity, tunable morphologies, structural diversities, and ability of room temperature (RT) sensing. This review summarizes the current advancement in various pristine MOF materials and their composites for different electrical transducer-based gas sensing applications. The review begins with a discussion on the overview of gas sensors, the significance of MOFs, and their scope in the gas sensing field. Next, gas sensing applications are divided into four categories based on different advanced transducers: chemiresistive, capacitive, quartz crystal microbalance (QCM), and organic field-effect transistor (OFET) based gas sensors. Their fundamental concepts, gas sensing ability towards various gases, sensing mechanisms, and their advantages and disadvantages are discussed. Finally, this review is concluded with a summary, existing challenges, and future perspectives. An overview of the MOF-based gas sensing materials with different electrical transduction principles.